2022
DOI: 10.3389/fnagi.2022.866336
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise-Induced Astrocytic Neuroprotection and Cognitive Improvement Through Primary Cilia and Mitogen-Activated Protein Kinases Pathway in Rats With Chronic Cerebral Hypoperfusion

Abstract: Chronic cerebral hypoperfusion (CCH) is closely related to vascular cognitive impairment and dementia (VCID) and Alzheimer’s disease (AD). The neuroinflammation involving astrocytes is an important pathogenic mechanism. Along with the advancement of the concept and technology of astrocytic biology, the astrocytes have been increasingly regarded as the key contributors to neurological diseases. It is well known that physical exercise can improve cognitive function. As a safe and effective non-drug treatment, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This finding proposes an unexplored signaling axis between mitochondria and primary cilia in astrocytes. Finally, a mouse model of chronic cerebral hypoperfusion displays neuro‐inflammation that causes reactive gray matter astrocytes and fewer, shorter cilia (Cao et al., 2022). The connections of cilia and neurological impairments provide tantalizing models and suggest that cilia may contribute to astrocyte function.…”
Section: Mainmentioning
confidence: 99%
“…This finding proposes an unexplored signaling axis between mitochondria and primary cilia in astrocytes. Finally, a mouse model of chronic cerebral hypoperfusion displays neuro‐inflammation that causes reactive gray matter astrocytes and fewer, shorter cilia (Cao et al., 2022). The connections of cilia and neurological impairments provide tantalizing models and suggest that cilia may contribute to astrocyte function.…”
Section: Mainmentioning
confidence: 99%
“…Pathological conditions trigger morphological, molecular, and functional changes in astrocytes that become reactive ( 55 ). According to reports, after 2VO, the rats presented reactive astrocytes with neurotoxic characteristics, but early physical exercise prevents this effect ( 20 , 56 ). In the present study, the number of astrocytes increased in the CA1 and CA3 subfields caused by 2VO, as assessed 7 days after the event, supporting the hypothesis that 2VO leads to neurotoxic reactive gliosis due to the ischemic insult.…”
Section: Discussionmentioning
confidence: 97%
“…This set of evidence is suggestive of neurotoxic astrogliosis, possibly modulated by oxidative and inflammatory agents. Disruption of primary astrocyte cilia can lead to gliosis and neuroinflammation ( 60 ), increasing the number of C3 (a marker for neurotoxic astrocytes)/GFAP-positive astrocytes in rats 2 months after 2VO ( 56 ). In the present study, the 2VO-trained animals also showed branched astrocytes in response to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…All of these functional and structural changes collectively lead to hypoperfusion at rest [ 23 ]. Therefore, chronic cerebral hypoperfusion (CCH) is acknowledged as the chief cerebral hemodynamic alteration of CBF dysregulation, which may lead to ischemic neuronal damage and varied degrees of cognitive deficits, such as VCID [ 24 ]. However, the precise pathophysiological mechanisms of CCH underlying VCID still remain a mystery.…”
Section: Cbf Regulation and Vcidmentioning
confidence: 99%